Menghadapi Tantangan Global Dalam Perencanaan Bisnis: Strategi Untuk Mengatasi Kompleksitas Pasar Global - Kevira Eris Andini; Clarissa Diva Elvaretta; Putry Meysa Selvina; Laura Faradina Wally; Rusdi Hidayat N; Maharani Ikaningtyas (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2024)
This research entitled "Facing Global Challenges in Business Planning: Strategies for Overcoming Global Market Complexity" has the aim of investigating and developing effective strategies for overcoming global market complexity in business planning. With ever-growing challenges in the global market, such as economic fluctuations, regulatory changes, and intense competitive dynamics, it is important for companies to have adaptive and effective strategies. Using literature reviews to collect and analyze data from various books, journals, and reports related to the research subject is the core of this qualitative research strategy. The term "international marketing" describes any type of advertising that reaches more than one country. It is common practice for entrepreneurs to write detailed documents outlining the history, current state, and future projections of their company. This document is known as a business plan. The findings of this research indicate that effective corporate planning techniques have a significant impact in overcoming global difficulties